2014
DOI: 10.1111/jdv.12556
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum paraoxonase and arylesterase activities in patients with rosacea

Abstract: Serum PON1 enzyme activities have decreased significantly in rosacea. These findings support that decreased PON1 activity and increased oxidative stress may play a role in the pathogenesis of rosacea. Further studies are needed to elucidate the role of PON1 activity in the pathophysiology of rosacea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 31 publications
4
58
0
Order By: Relevance
“…The inhibition of ROS activity in neutrophils with various topical and systemic drugs used in the treatment of rosacea supports the "oxidative stress phenomenon" hypothesis [7][8][9]. On the other hand, PON1 is an enzyme having antioxidant and anti-inflammatory activity and it was found that serum PON1 levels decreased in rosacea [10].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…The inhibition of ROS activity in neutrophils with various topical and systemic drugs used in the treatment of rosacea supports the "oxidative stress phenomenon" hypothesis [7][8][9]. On the other hand, PON1 is an enzyme having antioxidant and anti-inflammatory activity and it was found that serum PON1 levels decreased in rosacea [10].…”
Section: Introductionsupporting
confidence: 52%
“…Various studies showed decreased PON1 activity in systemic diseases including metabolic syndrome, atherosclerosis, diabetes mellitus and in various skin diseases such as psoriasis, recurrent aphtous stomatitis [22][23][24][25]. Takcı et al reported that PON1 activity (PON and ARES) is lower and serum lipid hydroxyperoxide levels are higher in rosacea patients indicating increased oxidative stress in rosacea [10].…”
Section: Discussionmentioning
confidence: 99%
“…4,13 Some of the common features of rosacea and psoriasis are dysregulation of cutaneous innate immunity and overexpression of cathelicidin, 1 type-1 helper T cells as the predominant activated immune cells, 13,14 and low serum PON1 activity. 9,15 These findings have also been reported in the process of atherosclerosis. 13,16,17 It is worth mentioning that elevated C-reactive protein level and low PON1 activity are known predictors of cardiovascular events after adjusting for other CVD risk factors.…”
Section: Discussionmentioning
confidence: 64%
“…The study showed that serum PON1 activity decreases significantly in patients with rosacea. 9 Interestingly, lower PON1 activity has also been demonstrated in dyslipidemic patients. 10 There was also evidence of reduced PON1 activities in patients with hypertension and DM.…”
Section: Discussionmentioning
confidence: 97%
“…Oxidative stress constitutes the basis of many inflammatory skin diseases. 3 Oxidative stress may have an important role in the pathogenesis of genital warts. Several studies have suggested that imbalances in the oxidant/antioxidant systems may play an important role in HPV infection.…”
Section: Introductionmentioning
confidence: 99%